MONITORAMENTO DA DEMANDA QUÍMICA DE OXIGÊNIO BASEADO EM GRÁFICO DE CONTROLE NÃO PARAMÉTRICO NPEWMA-SN - CRUZ, David Venancio da; CUNHA FILHO, Moacyr; PISCOYA, Victor Casimiro; CUNHA, Ana Luiza Xavier (Brazilian Journal of Biometrics, 2019)
Control charts of variables that indicate water quality and environmental degradation are important tools in environmental monitoring. However, not all of these variables meet the assumptions of the control charts, especially, regarding to normal distribution. An alternative approach is the non-parametric controls charts that do not require distribution knowledge and are effective in monitoring any continuous distribution. The objective of this work is to present a non-parametric control chart, based on signal testing (NPEWMA-SN) and, its advantages. This control chart is applied to non-normal variables related to the Chemical Oxygen Demand (COD), at a point on the São Francisco River, at the geographical coordinates of Latitude: -19 ° 49’54 "and Longitude: -45 ° 17’28 ". The results show that the NPEWMA-SN chart is the best alternative for the statistical control of non-normal processes, avoiding, even, the increase of the rate of false alarms.